2023
DOI: 10.3390/fishes8020061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System

Abstract: Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…So a negative correlation seems apt, moreover, suggesting the proper functioning of the units. The negative role of pH has been previously studied and the negative correlation seems fitting (Majhi et al 2023). However, TDS is a good determinant of biofloc and the negative correlation observed in our study could have been due to any water treatment process being performed (unknowingly) or a reduced organic load due to plankton-crash (Kazemi et al 2022).…”
Section: Discussionsupporting
confidence: 59%
“…So a negative correlation seems apt, moreover, suggesting the proper functioning of the units. The negative role of pH has been previously studied and the negative correlation seems fitting (Majhi et al 2023). However, TDS is a good determinant of biofloc and the negative correlation observed in our study could have been due to any water treatment process being performed (unknowingly) or a reduced organic load due to plankton-crash (Kazemi et al 2022).…”
Section: Discussionsupporting
confidence: 59%
“…Dunham and Elaswad [ 97 ] emphasized the significance of water quality, temperature, and dissolved oxygen levels in their review, suggesting that proper management of these factors can substantially improve overall welfare and productivity. Similarly, Majhi et al [ 98 ] demonstrated that the implementation of biofloc-based water treatment systems improved water quality, reduced stress, and enhanced growth performance, supporting the notion that ecological factors play a significant role in catfish welfare. Handling and transport are key areas where catfish welfare is paramount, as these processes can induce stress, compromising immune function and increasing disease susceptibility [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 90%
“…All these imply that conservation aquaculture has the potential to reverse the status of exploited fish stock in the wild by enhancing the natural populations and reducing the pressure on capture fisheries (Diana, 2009). Such efforts are required for the conservation and effective utilization of all state fish species, including C. chitala (Mitra et al, 2018), mahseer (NAAS, 2018Pinder et al, 2019), O. bimaculatus (Biswas et al, 2023), andT. ilisha (NAAS, 2018).…”
Section: Ex Situ Conservationmentioning
confidence: 99%